Thermal comfort and IAQ analysis of two Portuguese hospital buildings - Silva, Sandra Monteiro (2014)
In the last decades, public and governmental awareness on thermal comfort and indoor air quality (IAQ) has been growing. In buildings the number of potential pollutants is significant, and even low concentration levels can cause health problems (increased incidence of asthma and allergies, for example) if combined effects are considered. Therefore, the assessment of thermal comfort conditions and IAQ is very important to ensure health, wellbeing and productivity. This paper presents the results of a thermal comfort conditions and IAQ assessment of two hospital buildings with natural ventilation. The goal of this study was to verify the thermal and IAQ conditions inside Portuguese hospital buildings. The air temperature, the black bulb temperature, air velocity, relative humidity and the concentration of suspended particles, carbon dioxide, carbon monoxide, ozone, formaldehyde and total volatile organic compounds were measured. A standard questionnaire was delivered to the occupants to also obtain a subjective assessment of the thermal comfort and IAQ conditions. The results showed that, in general, the occupants were uncomfortable and that the main IAQ problems were related to high concentrations of carbon dioxide, volatile organic compounds and formaldehyde.